Kulturowo-religijny wymiar tatuażu w Koptyjskim Kościele Ortodoksyjnym - Pruszczyńska, Dominika (Łódzkie Studia Teologiczne, 2024)
The difficulties of practicing one’s religion in the context of persecution have had and continue to have a significant impact on the formation of religious and social attitudes. This article presents the process of forming the religious identity of the Christian community in the face of persecution, using the example of the Coptic Orthodox Church. The analysis of this process aims to come closer to answering the question of how the sense of constant struggle for survival and preservation of faith affects this process in the face of religious persecution. The main issue of the article under discussion is the analysis of the ritual of religious tattooing. This ritual not only symbolizes devotion, but also represents a tangible expression of opposition to the threat of forced conversion or martyrdom during turbulent periods of persecution. The article aims to contribute to a deeper understanding of the complex interaction between religious identity formation and persecution in the Christian community.